RECEPTION ANALYSIS OF FORMER STREET CHILDREN FILM ALANGKAH LUCUNYA NEGERI INI - Jaka Farih Agustian; Dr. Andria Saptyasari; Dr. Silviana Purwanti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Alangkah Lucunya Negeri Ini (ALNI) describe social problems about street children that occur in Indonesia. The film attempts to construct street children as marginalized groups, through discourses on social discrimination, verbal and non-verbal violence, and the role of crime. The role shown by street children in the ALNI film provides a reflection related to the lives of former street children in the past. Former street children are in a marginalized position and get negative stigma in social interaction.. The purpose of this study is to see, understand, and explore how former street children response, expression, comment, or interpret meaning in watching the ALNI film played by the street child. This study uses the reception method proposed by Stuart Hall, namely the concept of dominant hegemony, negotiation, and opposition. The results showed that in addition to the appearance of pleasure in watching through the comedy genre in film, pleasure also displayed distortions due to verbal and non-verbal violence displayed in the ALNI film. The element of pleausure in the watch activity is done by expressing happiness, sadness, and frustration when watching a film. Some informants explained the film's presence as a form of effort to boost the development of the lives of street children and as a motivation for street children to put awareness of the educational and religious construction contained in the film. However, the construction of crime aimed at street children in the film also creates ambivalence and contradiction, as a result of the experience of society stigma that is increasingly inherent in the lives of street children. The construction of the film in building the role of street children also provides personal closeness in remembering street children who were present in life in the past.